The Scientific Evolution of Astronomy: From Earth-Centered Universes to an Expanding Cosmos - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2026)
The development of astronomical models has been central to humanity's understanding of the cosmos, evolving from the ancient geocentric model to the modern-day heliocentric and elliptical models. This progression reflects the advancement of observational techniques and mathematical formulations, each model providing insights that led to a more accurate depiction of planetary motion. The purpose is to explore the historical shift from the geocentric to the heliocentric and Keplerian models, examining their impact on astronomy and the broader implications for scientific progress. The research employs a historical analysis of astronomical theories, supplemented with Python-based simulations, to visualize each model’s key features. The study finds that the transition from the Earth-centered view to a Sun-centered one, followed by the refinement of planetary motion into elliptical orbits, marked a turning point in scientific thought. The results demonstrate how Kepler's elliptical model offers the most realistic depiction of planetary motion and how the heliocentric model is humbler than the geocentric model with epicycles. The significance of these models in providing the groundwork for contemporary physics and astronomy is emphasized in the conclusions. The analysis encourages more multidisciplinary research and technological advancements in space flight to continue building upon these core concepts.